Genome‐wide nuclear data confirm two species in the Alpine endemic land snail Noricella oreinos s.l. (Gastropoda, Hygromiidae). (24th January 2020) - Bamberger, Sonja; Duda, Michael; Tribsch, Andreas; Haring, Elisabeth; Sattmann, Helmut; Macek, Oliver; Affenzeller, Matthias; Kruckenhauser, Luise
Abstract: The Austrian endemic land snail species Noricella oreinos (formerly Trochulus oreinos ) occurs in the Northeastern Calcareous Alps at high elevations. Two morphologically highly similar subspecies N. o.   oreinos and N. o. scheerpeltzi have been described. First analyses of mitochondrial and nuclear marker sequences indicated a high genetic divergence between them. In the present study, we aimed to assess gene flow between the two subspecies which should help to re‐evaluate their taxonomic status. Sequence data and amplified fragment length polymorphism (AFLP) markers of 255 Noricella specimens covering the whole distribution range were analyzed. A clear geographic separation was found within the potential contact zone, the Haller Mauern mountain range. Samples of all western sites were part of the clade representing N. o. scheerpeltzi and almost all samples from the eastern sites clustered with N. o. oreinos . However, within two sampling sites of the eastern Haller Mauern, a few individuals possessed a COI sequence matching the N. o. oreinos clade whereas at the ITS2 locus they were heterozygous possessing the alleles of both taxa. Contrary to the ITS2 results indicating historical and/or ongoing hybridization, AFLP analyses of 202 individuals confirmed a clear separation of the two taxa congruent with the mitochondrial data. Although they occur on the same mountain range without any physical barrier, no indication of ongoing gene flow between the two taxa was found. Thus, we conclude that the two taxa are separate species N. oreinos and N. scheerpeltzi . Abstract : We provide insights into the land snail genus Noricella endemic to the Northeastern Austrian Alps. Based on a nuclear multilocus dataset, a clear separation of the two subspecies of N. oreinos was found. This investigation included individuals from the whole distribution range focussing on the potential hybrid zone. Our finding corroborates previous results of mitochondrial DNA barcodes and genital anatomy, which showed the distinctness of both forms. Thus, we conclude that Noricella oreinos and Noricella scheerpeltzi are separate species.